1995
DOI: 10.1111/j.1530-0277.1995.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Reproductive Competence at an Earlier Age in Female Rats Exposed Prenatally to Ethanol

Abstract: Previous studies have shown that prenatal ethanol exposure can partially masculinize or defeminize neurobehavioral development of female rats. An early age of onset of anovulation is one of the primary characteristics of partial defeminization. Consequently, we examined the occurrence of anovulation in fetal alcohol-exposed (FAE) female rats at 2, 6, and 12 months of age using both vaginal cytology as well as wheel-running behavior. We assessed the ability of estrogen and progesterone to elicit proprioceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…It has been argued that cognitive and behavioral abnormalities produced by prenatal ethanol exposure may be masked in young-adult animals because of compensatory mechanisms or strategies, but that these compensatory mechanisms may break down due to stressful situations, complex testing procedures, or aging (Riley, 1990). Of particular relevance to the performance of mid-aged E animals in the present study, previous research has shown that E animals exhibit behavioral and hormonal hyperactivity to stress (Angelogianni & Gianoulakis, 1989;Nelson et al, 1986;Osborne et al, 1980;Taylor et al, 1982;Weinberg, 1988Weinberg, , 1992Weinberg, , 1993 as well as accelerated aging, including a shortened life span (Abel et al, 1987) and an earlier loss of reproductive function in E female rats (McGivern et al, 1995). These factors were expected to affect spatial learning and memory negatively in mid-aged E animals.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It has been argued that cognitive and behavioral abnormalities produced by prenatal ethanol exposure may be masked in young-adult animals because of compensatory mechanisms or strategies, but that these compensatory mechanisms may break down due to stressful situations, complex testing procedures, or aging (Riley, 1990). Of particular relevance to the performance of mid-aged E animals in the present study, previous research has shown that E animals exhibit behavioral and hormonal hyperactivity to stress (Angelogianni & Gianoulakis, 1989;Nelson et al, 1986;Osborne et al, 1980;Taylor et al, 1982;Weinberg, 1988Weinberg, , 1992Weinberg, , 1993 as well as accelerated aging, including a shortened life span (Abel et al, 1987) and an earlier loss of reproductive function in E female rats (McGivern et al, 1995). These factors were expected to affect spatial learning and memory negatively in mid-aged E animals.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, not only may impaired performance on spatial learning and memory tasks in E animals be related to stress-induced performance deficits associated with increased HPA activity but aging E animals also may experience an accelerated rate of impairment in hippocampal-mediated functions. Although this remains to be investigated, research demonstrating accelerated aging in E animals, including a shortened lifespan in E animals (Abel, Church, & Dintcheff, 1987) and an earlier loss of reproductive function in E female rats (McGivern, McGeary, Robeck, Cohen, & Handa, 1995), alludes to the possibility that E animals may experience an increased rate of aging for physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…The reason(s) for these sexually dimorphic changes is unclear, but it is possible that these behavioral patterns may be related to females reaching hormonal and physical markers of puberty prior to males [60]. Prenatal ethanol exposure may shift the onset of these developmental stages and thereby alter sex-hormones and brain development [61, 62]. …”
Section: Discussionmentioning
confidence: 99%
“…Our unpublished data also indicated that PAE females: (1) did not show an increase in E 2 levels as a function of age, resulting in lower E 2 levels relative to control females; (2) demonstrated a lag in the age-related increase of P 4 levels observed in controls; (3) failed to show a similar increase in PRL and LH levels as a function of age as reported in controls; and (4) had lower levels of PRL and LH (Sliwowska et al, unpublished data). These alterations may in turn lead to early incidence of acyclicity, an indication of premature reproductive aging [78]. As hormone levels fluctuate during the day, it is worth noting that blood was collected between 9:00 and 12:00 h. Thus, together with delayed onset of puberty, the reproductive window -at least in animal models of PAE -may be shorter.…”
mentioning
confidence: 99%